Long-Term Results of Surgical Treatment of Pulmonary Embolism (PE) by Balloon Angioplasty (BAP) in Combination with Thrombolytic Therapy - M. V. Davydenko; N. A. Trofimov; A. G. Dragunov; I. P. Efimova; N. I. Kiseleva; N. A. Shatilova; O. A. Shipunova; A. A. Sibirtsev (Креативная хирургия и онкология, 2019)
Introduction. Pulmonary Arterial Thromboembolism (PATE), which is characterised by low prognosis probability and potentially high danger, ranks third in the mortality structure of cardiovascular diseases. The primary method for treating PATE is recanalisation of the pulmonary arteries affected by embolism. Although the destruction of thromboemboli with thrombolytic drugs has proven effective, the right ventricular failure progresses faster in a majority of patients with massive pulmonary embolism. The aim of the present study is to evaluate the long-term results of surgical treatment of PATE by balloon angioplasty in combination with thrombolytic therapy in comparison with isolated systemic thrombolysis.Materials and methods. The treatment of 80 patients with pulmonary embolism was analysed. Depending on the selected treatment approaches, the patients were divided into 2 groups as follows: group 1 — 39 patients, conducted by the BAP LA, in combination with thrombolysis; group 2 — 41 patients who underwent conservative treatment (thrombolysis and subsequent anticoagulation therapy).Results. Despite the small sample and short period of observation, we may note the significantly better results of treatment in group 1 of the study. Positive dynamics of ECG indicators — in particular, pulmonary hypertension, RV KDR, functional class of heart failure NYHA as well as the reduction of right ventricular overload according to the ECG — indicates that the BAP LA method for the surgical treatment of pulmonary embolism, in combination with thrombolytic therapy, is effective and safe.Conclusions. Balloon angioplasty of pulmonary arteries in combination with thrombolytic therapy can significantly reduce the degree of pulmonary hypertension (рχ2 = 0.034), as well as helping to normalise the size of the right ventricle (рχ2 < 0.001) and improvement in functional class of heart failure NYHA (рχ2 = 0.026) in patients with pulmonary embolism compared with patients with isolated thrombolytic therapy.